2021
DOI: 10.1007/s00723-021-01371-w
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Reaction Conditions for the Formation of Fumarate via Trans-Hydrogenation

Abstract: Parahydrogen-induced polarization is a hyperpolarization method for enhancing nuclear magnetic resonance signals by chemical reactions/interactions involving the para spin isomer of hydrogen gas. This method has allowed for biomolecules to be hyperpolarized to such a level that they can be used for real time in vivo metabolic imaging. One particularly promising example is fumarate, which can be rapidly and efficiently hyperpolarized at low cost by hydrogenating an acetylene dicarboxylate precursor molecule usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 75 publications
0
17
0
Order By: Relevance
“…182 It has since been reported that this has been increased to 30–45% by optimisation of the equipment, reaction conditions, and purification procedure (precipitation as a solid before redissolving). 183,184 The great benefit of this approach is that it is highly compatible with biological imaging studies as it can produce aqueous solutions of hyperpolarised fumarate without contaminant side products or toxic catalyst. 107,183 Production and injection of PHIP-hyperpolarised [1- 13 C]-fumarate into mice containing acetaminophen-induced hepatitis has allowed fumarate biochemistry to be examined in vivo using 2D chemical shift imaging at 1.5 T (Fig.…”
Section: Applications Of Novel Phip Catalysts In Hyperpolarisationmentioning
confidence: 99%
“…182 It has since been reported that this has been increased to 30–45% by optimisation of the equipment, reaction conditions, and purification procedure (precipitation as a solid before redissolving). 183,184 The great benefit of this approach is that it is highly compatible with biological imaging studies as it can produce aqueous solutions of hyperpolarised fumarate without contaminant side products or toxic catalyst. 107,183 Production and injection of PHIP-hyperpolarised [1- 13 C]-fumarate into mice containing acetaminophen-induced hepatitis has allowed fumarate biochemistry to be examined in vivo using 2D chemical shift imaging at 1.5 T (Fig.…”
Section: Applications Of Novel Phip Catalysts In Hyperpolarisationmentioning
confidence: 99%
“…It is been reported that sodium sulfite improves the selectivity of the trans hydrogenation reaction, although the mechanism of its action is not yet known. 33 , 60 …”
Section: Materials and Methodsmentioning
confidence: 99%
“…In the next step, the dependence of the fumarate production on temperature, pH, and sodium sulfite concentration was determined. Employing these optimized conditions, proton enhancement factors of 3500 at 500 MHz, corresponding to polarizations of P ( 1 H) = 28%, were obtained (for details see Wienands et al 78 ).…”
Section: Applications Of Parahydrogen In Nmrmentioning
confidence: 99%
“…Budker and coworkers have proposed parahydrogen based ultralow-eld NMR techniques as part of the cosmic axion spin precession experiment (CAS-PEr), 68 an NMR-based dark-matter search to probe the axionfermion "wind" coupling. 69 Both PHIP and SABRE have a high application potential in the eld of hyperpolarized MRI, 63,[70][71][72][73][74][75][76][77][78] where hyperpolarized substances, such as hydroxyethyl propionate, fumarate or succinate, were employed as contrast agents (see e.g. the reviews by Hövener et al, 79 Reineri et al 80 and Aime et al 81 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation